Antibody against chromatin assembly factor-1 is a novel autoantibody specifically recognized in systemic lupus erythematosus. (September 2014) - Doe, K; Nozawa, K; Hiruma, K; Yamada, Y; Matsuki, Y; Nakano, S; Ogasawara, M; Nakano, H; Ikeda, T; Ikegami, T; Fujishiro, M; Kawasaki, M; et al.
Autoantibodies to proliferating cell nuclear antigen (PCNA) are specifically, if rarely, present in systemic lupus erythematosus (SLE) patient sera. Even SLE patients lacking PCNA reactivity often show reaction to PCNA-binding protein. Here, immunoreactivity to chromatin assembly factor-1 (CAF-1), an essential molecule for DNA replication and a PCNA-binding protein, was compared for the sera of SLE patients, normal healthy controls (NHCs) and other disease controls, and in autoimmune sera reactive to standard autoantigens, by enzyme-linked immunosorbent assay (ELISA), indirect immunofluorescence, and immunoblotting. CAF1 and IRF1 expression in SLE and NHC peripheral mononuclear cells were compared by quantitative real-time polymerase chain reaction. Serum interferon-γ-inducing protein-10 and anti-double-stranded (ds)DNA antibody levels were measured by ELISA. Increased CAF-1 autoimmune reactivity was recognized in SLE or serum anti-dsDNA antibody-positive patients. Significantly greater central nervous system (CNS) involvement (aseptic meningitis) and serum anti-dsDNA antibody titers were present more often in anti-CAF-1 antibody-positive than antibody-negative SLE patients. IFN-γ positively regulated CAF-1 expression in vitro and was associated with anti-CAF-1 antibody production in SLE. Thus, a novel anti-CAF-1 autoantibody is frequently found in patients with SLE and is a useful biomarker for diagnosis, especially in cases with CNS involvement. Aberrant IFN-γ regulation appears to play an important role in anti-CAF-1 antibody production in SLE.